PERALIHAN STATUS PENANGGUNG MENJADI PEMEGANG HIPOTIK DI DALAM PEMBAYARAN HUTANG - Adi Saputra, I Gede Oki; Mudana, I Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2021)
In the current global developments "transitional status of the person becomes the holder of mortgages in the payment of debt" arising from the presence of an engagement is a common thing. The switch is aimed to identify whether the fiduciary also switch to the insurer with the payment of debt and clearly understand the recipient Fiduciary responsibility for the consequences of law or neglect the use and transfer of objects fiduciary fiduciary by the grantor. This study uses normative research. Basically, the conclusion of this study is Fiduciary given as collateral to creditors will also switch to the insurer by the subrogation, as is the case with a lien pursuant to Article 19 paragraph 1 of Law Fiduciary. As for the receiver fiduciary responsibility due to legal or negligence in the use of objects Fiduciary by that in accordance with Article 24 of the Law states that fiduciary responsibilities and risks associated with the use and transfer of objects into objects in the hands of fiduciary fiduciary giver. Keyword : transitional, debt, fiduciary, subrogation